Review of new biological drugs and JAK inhibitors approved for children and adolescents with moderate to severe atopic dermatitis: the situation in Uruguay (Archives of Pediatrics of Uruguay, 2026)
Atopic Dermatitis (AD) is a chronic inflammatory disease that predominantly affects children and adolescents, with a significant impact on their quality of life and psychosocial well-being. The majority of patients with atopic dermatitis have mild forms and improve with hygiene measures and topical treatments, but 5–20% are moderate or severe, and in these cases, other interventions are required. Until a few years ago, immunosuppressants such as systemic corticosteroids, cyclosporine, azathioprine, mycophenolate mofetil, and methotrexate were the only systemic treatment options available for patients with moderate or severe AD, but presently, other therapeutic options exist for these patients, such as biological drugs or JAK inhibitors, among others. This paper aims at reviewing recent advances in the treatment of AD, specifically focusing on these new biological drugs and JAK inhibitors approved for the treatment of moderate to severe AD in children and adolescents, with special attention to the drugs used and available in Uruguay.
Keywords: Dermatitis Atopic; Janus Kinase Inhibitors; Biological Products